2021
DOI: 10.1371/journal.pone.0261013
|View full text |Cite
|
Sign up to set email alerts
|

Maternal opioid use is reflected on leukocyte telomere length of male newborns

Abstract: Opioid use accelerates normal aging in adults that raises a question on whether it may trans-generationally affect aging and aging biomarkers in the offspring of users as well? In the present research, we investigated the relative telomere length in umbilical cord blood of newborns born to opioid consuming mothers compared to normal controls. Telomere length shortening is a known biomarker of aging and aging related diseases. Its measure at birth or early in life is considered as a predictor of individual heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Further investigation is required to assess whether the difference between cord blood cells and the placenta may be the reason for the difference in our results. Research has shown that environmental factors such as exposure to pollution, tobacco smoking and drug consumption 35 during pregnancy impacts the telomere length and the mitochondrial DNA copy number at birth 36 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation is required to assess whether the difference between cord blood cells and the placenta may be the reason for the difference in our results. Research has shown that environmental factors such as exposure to pollution, tobacco smoking and drug consumption 35 during pregnancy impacts the telomere length and the mitochondrial DNA copy number at birth 36 40 .…”
Section: Discussionmentioning
confidence: 99%
“…While not toxins per se, intrauterine exposure to substances with abuse liability (alcohol, nicotine, opioids) is readily modeled in rodents and can be combined with postnatal models [85][86][87]. Clinically, perinatal exposure of infants to opioids (including methadone) can have profound and lasting negative effects on the central nervous system via altered inflammatory and neuroinflammatory trajectories [88,89]. This negative neuroinflammatory impact is also seen in rodent models of perinatal opioid exposure [90][91][92].…”
Section: A Sampling Of Animal Models For Developmental Brain Injurymentioning
confidence: 99%